Antifungal applications for nano-additives synthesized with a bio-based approach - Gámez Espinosa, Erasmo (2020)
Filamentous fungi are microorganisms that cause deterioration of structural materials due to their ecological plasticity and vegetative functions. Functionalised sol-gel based products can be used to control this kind of biodeterioration through the association to antifungal active additives which are trapped in the siloxane crosslinking. Bioactive additives and materials to control microbial growth have been gaining more attention over the years. However, due to the concern about their toxicity, bio-based approach has been explored. The aim of the present research was to obtain antifungal additives with nanoparticles synthesised with aqueous extract of Senna occidentalis L and silver or copper salts to obtain a functionalised sol-gel based product to control the biodeterioration of bricks. Nanoparticles were characterised by UV–vis spectroscopy, transmission electron microscopy and x-ray diffraction. Silver nanoparticles (15 nm) showed higher stability over time and proved to be active against Aspergillus versicolor and Cladosporium cladosporioides which were isolated from brick wall. The strains were selected due to their high frequency in mycobiota of biodeteriorated structural building materials. The silver nanoparticles were successfully integrated in a silane-based matrix to be applied in bricks. The samples were characterised by surface tension determination, contact angle measurement, water absorption determination, scanning electron microscopy and energy dispersive x-ray spectroscopy. Bricks with the lower concentration (2%) of the functionalised silane (3- mercaptopropyltrimethoxy) showed to be efficient to prevent fungal biofilm development with 100% of inhibition against both strains.